Export growing among knowledge-intensive service providers - Alexander Eickelpasch (Weekly Report, 2011)
In the German economy, both international trade in goods and also in services have grown quite forcefully. World-wide Germany is the third-largest exporter of services. However, until recently little has been known about the export behavior of service companies, especially small and medium sized enterprises (SME). The exports of SMEs in knowledge-intensive service branches have grown in above average in the years 2003 to 2007. Admittedly, the quotient of exports of these companies is still smaller than that of the large companies. The proportion of companies exporting has increased among both SMEs and large companies. The increase however was especially pronounced among medium-sized companies. A longitudinal study for the period 2003 to 2007 shows that there are relatively few small companies that constantly export, i.e. in all of the years named here. Among the medium-sized companies there are many that - unlike the case of very small companies - first began exporting in these years. The significance of the first-time exporter exceeds the significance of those who have ended their shipments abroad.
Keywords: F14; F23; L80; 330; export; knowledge-intensive services; small and medium sized enterprises